Stage of Change and Motivation to a Healthier Lifestyle before and after an Intensive Lifestyle Intervention - Buratta Livia; Reginato Elisa; Ranucci Claudia; Pippi Roberto; Aiello Cristina; Sbroma Tomaro Emilia; Perrone Chiara; Tirimagni Alberto; Russo Angelo; De Feo Pierpaolo; Mazzeschi Claudia (Hindawi Limited, 2016)
Objective. Lifestyle modification programs are different but typically include both nutritional aspects and physical activity as main domains with different behavioral and/or psychological strategies designed to affect change. A fundamental role in modifying unhealthy habits is played by personal motivation for change. The present study sought to investigate, in a group of 100 overweight/obese outpatients with and/or without TMD2, treatment seeking, the effect of an intensive lifestyle program on medical measures and motivational profile for physical activity (PA) and healthy nutrition (NUTR). Method. Subjects participated in an intensive multidisciplinary lifestyle intervention at C.U.R.I.A.MO. Before and after the intervention, patients received a comprehensive evaluation of their clinical, anthropometric, and metabolic states and motivation to lifestyle changes. Results. Data showed differences before and after intervention in both medical and motivational measures. Before the intervention patients reported to be ready, open, and determined to change and gave importance to healthy habits. After the intervention patients continued to be determined but increased the actions toward the change showing a higher degree of maintenance and of acquisition of habits especially in the physical domain of the new lifestyle. Conclusion. Data support the notion that the motivation should be followed during all the lifestyle interventions to support the change on both domains of the lifestyle program.